Assessment of Antihyperlipidemic and Antitumor Effect of Isolated Active Phytoconstituents from Apium graveolens L. through Bioassay-Guided Procedures. (4th March 2019) - Iyer, Deepa; Patil, U. K.
ABSTRACT: The seeds of A. graveolens yielded coumarin derivatives such as seselin, methoxsalen, and 3H-isobenzofuran-1-one through chromatographic separation techniques. The structure of the components has been established on the basis of spectral data analysis. The present study was undertaken to explore the antihyperlipidemic and antitumor effects of ethanolic extract and phytoconstituents of A. graveolens in rodents. Albino rats were administered intraperitoneal (i.p.) injection of Triton WR 1339 for the induction of hyperlipidemia at a dose of 400 mg/kg body weight. After 24 h of Triton administration, the test drugs were administered orally at dose of 50 mg/kg body weight in rats. The extract and isolated components were further investigated for the tumor take inhibitory activity in hybrid mice (of C57BL strain + Swiss albino strain). Preventive group animals were injected daily with the extract and isolated components at a dose of 50 mg/kg body weight i.p. for 10 consecutive days. The animals were observed for the growth of tumor after injection of B16F10 melanoma cells into the dorsal skin of mice. The study showed significant reduction in total cholesterol ( p < .001), triglycerides ( p < .001) and low-density lipoprotein (LDL) level ( b p < .01) and significantly increased high density lipoprotein (HDL) level ( p < .01) after the treatment. Pretreatment showed delay in tumor growth by increasing the volume-doubling time ( p < .01), growth delay ( p < .01), and mean survival time ( p < .001). Acute treatment caused stimulatory effect on HDL level and inhibition in total cholesterol (TC) and triglyceride (TG) elevation induced by Triton. Tumor regression studies showed a regression response for tumor growth in vivo of murine mouse melanoma tumor cell lines.